Crack Location in Wind Turbine Blades Using Vibration Signal and Support Vector Machine - Perla Y. Sevilla-Camacho; José B. Robles-Ocampo; Juvenal Rodríguez-Resendíz; Sergio De la Cruz-Arreola; Marco A. Zuñiga-Reyes; Edwin N. Hernández-Estrada (Vibration)
This study introduces a new method to locate cracks in wind turbine blades using the support vector machine algorithm and the tangential vibration signal measured at the root blade in static conditions. The method was implemented in hardware and experimentally validated on 200 W wind turbine blades. The blade conditions were healthy, and transverse cracked at the root, midsection, and tip. The experimental procedure is easy, and only one low-cost piezoelectric accelerometer is needed, which is affordable and straightforward to install. The machine learning technique used requires a small dataset and low computing power. The results show exceptional performance, achieving an accuracy of 99.37% and a precision of 98.77%. This approach enhances the reliability of wind turbine blade monitoring. It provides a robust early detection and maintenance solution, improving operational efficiency and safety in wind energy production. K-nearest neighbors and decision trees are also used for comparison purposes.